The right to disconnect in the employment relationship: in particular the Portuguese regime - Sousa Machado, Susana; Faria , Marta (Law, State and Telecommunications Review, 2025)
[Purpose] This article looks at the evolution of the right to disconnect in various countries, the European Union, Portugal [Methodology/approach/design] Through bibliographical research on disconnection, European and Chilean legal systems and the evolution of this right. [Findings] The right to disconnect is a relatively recent issue in labor law. Since 2017, there have been various ways of legislating for this right, but there is still a long way to go in terms of worker disconnection. Above all, it is necessary to change the mentality of employers and workers who look down on those who disconnect from work when their working hours end.